Study of the patterns, methods and impacts of the election according to the new constitution : case study Pattani Province - Tuansiri, Ekkarin; Thongfhua, Samart (King Prajadhipok’s Institute Journal, 2021)
This research article aims to study the local political movements during the 2019 general election in Pattani province. In order to understand political behavior under the new political rules established according to the 2017 Thailand constitution. This research is a qualitative research that set up an approach which focus on document research, interviews with the stakeholders in Pattani Province as the targeted area. The result of the research found that the new constitution has a direct impact to the candidates who run for the election such as the behavior of moving to the new political party. The establishment of a new party (Prachachat) just only to solve the specific local problems. The researchers found that the religion and culture affect the form and the campaigning to promote the candidates. The religious leaders and kinship in particular affects the voters especially in the suburb. The patronage system through the relationship that establishes the constituency also influences the people to choose their representative. The researchers found that the new generation enthusiasm in an media online effect their decision to choose by the Political party policy and their leadership as the important factors more than the old kinship In sensitive area. Therefore, the peace policies were presented by every political party to public, although, there are differences in details. The changing of media online landscape has resulted in the need of the candidates to adjust themselves to access more voters.